Estabilização de sistemas fuzzy T-S incertos usando realimenta̧ão derivativa - Pires Da Silva, Emerson Ravazzi [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Assunção, Edvaldo [UNESP]; Faria, Flávio Andrade [UNESP] (FapUNIFESP (SciELO), 2011)
In some practical problems, for instance, in the suppression of vibration in mechanical systems, the state-derivative signals are easier to obtain than the state signals. Thus, a method for state-derivative feedback design applied to uncertain nonlinear systems is proposed in this work. The nonlinear systems are represented by Takagi-Sugeno fuzzy models during the modeling of the problem, allowing to use Linear Matrix Inequalities (LMIs) in the controller design. This type of modeling ease the control design, because, LMIs are easily solved using convex programming technicals. The control design aimed at system stabilisation, with or without bounds on decay rate. The efficiency of design procedure is illustrated through a numerical example.
Stabilization of uncertain T-S fuzzy systems using statederivative feedback
Keywords: Fuzzy T-S Models; Linear Matrix Inequalities (LMIs); Parametric Uncertainties; State-Derivative Feedback; Control design; Controller designs; Convex programming; Decay rate; Design procedure; Fuzzy TS model; Mechanical systems; Numerical example; Parametric uncertainties; Practical problems; T S fuzzy system; Takagi Sugeno fuzzy models; Uncertain nonlinear systems; Controllers; Decay (organic); Design; Fuzzy systems; Linear matrix inequalities; Nonlinear feedback; Nonlinear systems; Stabilization; Vibrations (mechanical); State feedback